Interdisciplinary Approaches in Supporting Children at Risk - Mocanu, Lăcrămioara (Didactica Danubiensis, 2026)
Children at risk represent one of the most vulnerable social categories, requiring complex and coordinated interventions from multiple professional fields. This article explores how collaboration between social workers, psychologists, teachers, doctors, and legal specialists can contribute to the early identification of risk situations and the implementation of effective protection and recovery strategies. Through the analysis of specialized literature and international practices, the concrete benefits of the interdisciplinary approach are highlighted, such as improving communication between services, reducing overlaps of interventions, and increasing the efficiency of support programs. The study emphasizes the importance of continuous training of professionals in a collaborative spirit, the development of common work protocols, and the active involvement of families in the recovery process. The results indicate that only by integrating multiple perspectives and coordinating institutional efforts can real and sustainable protection be ensured for vulnerable children, giving them equal opportunities for harmonious development.